Prospective study of the usefulness of sural nerve biopsy. Issue 4 (1st October 2000) - Gabriel, C M; Howard, R; Kinsella, N; Lucas, S; McColl, I; Saldanha, G; Hall, S M; Hughes, R A C
Abstract : OBJECTIVE: This study aimed to determine the usefulness of sural nerve biopsy in neurological practice. METHODS: The first prospective study of sural nerve biopsy in 50 consecutive patients was undertaken. The investigating neurologist declared the prebiopsy diagnosis and management plan and after 3 months an independent neurologist evaluated the contribution of the biopsy to diagnosis and management. An independent audit officer sought information from the patient about the adverse effects and value of the biopsy after 6 weeks and 6 months. RESULTS: In seven cases the nerve biopsy changed the diagnosis, in 35 cases the biopsy confirmed the suspected diagnosis, and in eight cases the biopsy was non-contributory. The biopsy either changed or was helpful in guiding patient management in 60%, especially those with demyelinating neuropathy and multiple mononeuropathy. Seven patients reported having had infection and 10 reported increased pain at the biopsy site 6 months later. CONCLUSION: In a consecutive series of 50 cases, sural nerve biopsy altered the diagnosis in 14%, affected management in 60%, and caused persistent increased pain at the biopsy site in 33%.